Sejarah Penulisan Al-Qur’an (Kajian Antropologi Budaya) - Ibrahim, Nasruddin (Rihlah: Jurnal Sejarah dan Kebudayaan, 2015)
The Koran is the words of God revealed to the Prophet Muhammad through Gabriel, was intended to read and study it as a worship, which begins with al-Fatihah, and closed with an-Nas. The Qur’an doesn’t only for the Prophet, but also for his people (humans). Anthropological study has intent to understand more deeply about human involvement in the course of writing the Koran down to us today. Since the Prophet was still alive, the writing of the Qur’an had many improvements until today. Especially, the development of punctuation, so everyone can easily to read it and unify the way of reading by adding punctuation, without reducing and adding the verse. The reading way had standardized, only the dialects from every nation who read the Koran not the same. It happened because, in the anthropological side, it didn’t allowed for unify the dialects. Umar ra proposed to Abu Bakr ra to collected Koran into a mushaf from various media and then put it together and compiled it based on surah which had revealed to the Prophet. Collecting or copying the Koran had conducted because the intent of it to give a copies to the areas which was dominated by Islam, in an attempt to minimized the differences of reading way, because of the differences in readings every place due to factors of dialect and of course different language. Furthermore, after Khulafaurrasyidin gave the punctuation to the Koran which is the result of creativity and diligence in order to avoid mistakes in the reading of the Koran. <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: center; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" align="center"><span style="font-size: 12.0pt; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: ’Times New Roman’; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi;">SEJARAH PENULISAN ALQURAN <span style="font-size: 12.0pt; line-height: 107%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: ’Times New Roman’; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">(Kajian Antropologi <span style="font-size: 12.0pt; line-height: 107%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: ’Times New Roman’; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IN">Budaya<span style="font-size: 12.0pt; line-height: 107%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: ’Times New Roman’; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">)